MULHERES GUARANI ENCARCERADAS: as fronteiras dos Direitos Humanos - Adriane da Silva Oliveira (2023)
This work addresses the prisoners` reality of Guarani and Kaoiwá women in Mato Grosso do Sul, Brazil, from an ethnic and gender perspective, looking through the limitations of the protection and guarantee of rights by the State. This investigation is chronologically situated in the period between 2005 and mid-2022. During this period, it was evidenced a gradual increase in the female prison population, driven by various factors that affect the lives of these ethnic groups. It should be noted that the people to which these groups belong live in constant conflict over land ownership, generating numerous violations of rights by non-indigenous people. It must be added that these locations are overcrowded indigenous reserves created by the State. Within this ethnic group, women play a fundamental role in their community, who are directly affected by this punitive phenomenon, which, in turn, generates a disconnection, as well as distancing, marginalization and separation from their people. Therefore, the following question arose: what are the predominant factors in this increase of this incarcerated population? To answer this problem, it is necessary to understand what are the factors that during this period influenced the increase in incarceration of this group and how the protection and guarantee of (human) rights were applied. The following specific objectives were defined to contextualize and briefly present the reality of the Guarani and Kaiowá peoples: their history, culture and cosmos perception, and mainly the role of the women; to describe the coloniality implicit in the history of women's imprisonment in Brazil, in quantitative relation to the state of Mato Grosso do Sul, from a chronological, ethnic and gender perspective, thus signaling the factors that contribute to the increase of imprisonment and the limitations of (human) rights for this specific groups in this region. The methodology used is based on field research, concomitant with an interdisciplinary, bibliographical, exploratory, and descriptive investigation, using the historical and the deductive method. Our theoretical references was: Andria Caroline Angelo Santin, Angela Davis, Clara de Almeida Barbosa, Graciela Chamorro, Juliana Borges, Lauriane Seraguza, Nívia Maria TrindadeSantos, among others.